Genotoxicity of nanomaterials: Refining strategies and tests for hazard identification. (21st March 2013) - Pfuhler, Stefan; Elespuru, Rosalie; Aardema, Marilyn J.; Doak, Shareen H.; Maria Donner, E.; Honma, Masamitsu; Kirsch‐Volders, Micheline; Landsiedel, Robert; Manjanatha, Mugimane; Singer, Tim; Kim, James H.
<x xml:space="preserve">Abstract</x> A workshop addressing strategies for the genotoxicity assessment of nanomaterials (NMs) was held on October 23, 2010 in Fort Worth Texas, USA. The workshop was organized by the Environmental Mutagen Society and the International Life Sciences Institute (ILSI) Health and Environmental Sciences Institute. The workshop was attended by more than 80 participants from academia, regulatory agencies, and industry from North America, Europe and Japan. A plenary session featured summaries of the current status and issues related to the testing of NMs for genotoxic properties, as well as an update on international activities and regulatory approaches. This was followed by breakout sessions and a plenary session devoted to independent discussions of in vitro assays, in vivo assays, and the need for new assays or new approaches to develop a testing strategy for NMs. Each of the standard assays was critiqued as a resource for evaluation of NMs, and it became apparent that none was appropriate without special considerations or modifications. The need for nanospecific positive controls was questioned, as was the utility of bacterial assays. The latter was thought to increase the importance of including mammalian cell gene mutation assays into the test battery. For in‐vivo testing, to inform the selection of appropriate tests or protocols, it was suggested to run repeated dose studies first to learn about disposition, potential accumulation, and possible tissue damage. It was acknowledged that mechanisms may be at play that a standard genotoxicity battery may not be able to capture. Environ. Mol. Mutagen. 54:229–239, 2013. © 2013 Wiley Periodicals, Inc.